Adenoid Cystic Carcinoma of the Lacrimal Gland in a 36 year Old Male - ORAIN, Edward Paul P; HERNANDEZ, - TAN; Jo, Anne (Journal of Ophthalmic Science, 2023)
A case of lacrimal gland adenoid cystic carcinoma in a 36‑year‑old male is presented. The report reviews imaging, histopathology, perineural invasion risk, and multimodal management including surgery and radiotherapy.
Keywords: Adenoid cystic carcinoma; lacrimal gland; tumor